let S be the Unit Step function(adsbygoogle = window.adsbygoogle || []).push({});

for a function with a finite jump at t0 we have:

(*) L{F'(t)}=s f(s)-F(0)-[F(t0+0)-F(t0-0)]*exp(-s t0)]

so:

L{S'(t-k)}=s exp(-s k)/s-0-[1-0]*exp(-s k) = 0 & k>0

but S'(t-k)=deltadirac(t-k) and we know that L{deltadirac(t-k)}=exp(-s k)

so why do I get ZERO when using the formula (*)

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Laplace transform of dirac delta function

**Physics Forums | Science Articles, Homework Help, Discussion**